Obsoles[S]ence: recharting humanities relationship with technology through the adaptive reuse of the Kelvin Power Station - Pescivolo, Enrico (My University, 2022)
The only consistency is change. Power stations have long been associated with environmental destruction and global climate change. These concerns have of course been noted and global efforts have begun to mitigate a global catastrophe from climate change. With global populations expanding and economies emerging, access to sustainable technologies becomes increasingly difficult and the task of meeting energy demands and global goals with it. There is a collaborative need for innovation to combat these solutions while time is still available. Technology, while integral to advances, have also been instruments to our destruction. Technology has not only caused an immediate environmental threat, but an existential threat. There is therefore a need to alter humanities attitudes towards technology to foster innovation and combat climate change, remedying immediate issues while safeguarding the future. Kelvin Power Station, located in Kempton Park, stands in isolation from the urban fabric symbolizing a schism between technology, humanity and nature. Kelvin A station stands dormant and a threat to the urban fabric due to its retirement. To occupy and discard are technological methods of the past, where the threat of climate change extends into the threat of urban blight and the essence of being. Humanity thus has an opportunity to course correct attitudes towards technology: actively taking steps towards climate solutions while safeguarding the urban fabric and future attitudes. Phase one results in the adaptive reuse of the existing Kelvin A station into a centre for innovation and art as a catalyst for a future precinct conversion where a celebration of nature, humanity and technology exists. Not only does this celebrate the project intention, but also remedies the urban fabric by making a previously isolated and singular use site into a mixed-use site where different schools of thought and activity intersect. Innovation encompasses technological works towards global solutions where art grounds humanity and injects creativity into technology. By constructing off the past, the new centre begins humanity’s journey towards positive interactions with technology, nature and oneself. The change humanity experiences through evolution is witnessed through the change of space previously catering to technology of the old into a space of innovation for the new, symbolizing an evolutionary step and the beginnings of re-charted technological attitudes.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Architecture (Professional) to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, 2021